Geology and petrology of plutonic rock in Kuala Krai, Kelantan - Siti Syarifah Azri (2021)
The thesis is related to geology and petrology of plutonic rock in the study area of Kuala Krai, Kelantan. This study area is covered 25 Km2. The objectives of this study is to generate detail geological map with the scale of 1:25000 and study the origin of the plutonic rocks in the study area based on petrography analyses. From the analysis using the secondary data, the study area consists of various types of rocks such as sedimentary rocks, igneous rocks and metamorphic rocks from 299 to 251 million years ago to date that is alluvial, microgranite, granite, metasediment and phylite. Comparison of plutonic rock between rock in Berangkat Pluton (Mohd Rozi Umor et al,2012) and Stong Complex in Kelantan (Ramdanshah & Mohd Rozi, 2001). Both are using the X-Ray Diffraction method to get data of major element and trace elements. XRF is non-destructive analytical tool used to test the fundamental structure of materialsThere are nine samples of different rock types taken in Berangkat Pluton (Mohd Rozi Umor et al,2012) while eight samples also from different rock types taken in Stong Complex (Ramdanshah & Mohd Rozi, 2001). Harker diagram is generated to an analysis, comparison between trace element and a major element in both places.